Connecting theory with practice: Time to explore social reality and rethink resilience among health professionals. Issue 6 (23rd September 2020) - Aburn, Gemma; Hoare, Karen; Adams, Peter; Gott, Merryn
Abstract: Aim: To discuss and contrast different theoretical perspectives of resilience and explore the value these bring to understanding health professional well‐being. Background: Resilience has been used to describe one characteristic of health professionals who work in challenging areas, such as intensive care units, emergency departments and oncology settings. Studies have reported on how health professionals can become more resilient in these settings—with a focus on individuals—describing the conditions needed to become more resilient. Design: This is a Discussion paper. Data Sources: This paper draws on the extant literature to explore theoretical perspectives of social constructionism and social constructivism. These perspectives are then linked to recent literature to support the discussion of how resilience can be understood and considered in the context of health professionals. Implications for Nursing: Resilience is typically conceptualized at an individual level. This manuscript highlights the broader structural factors which impact health practitioner well‐being. The benefits of a resilient workforce are known to have an impact on the quality of patient care. Conclusion: This paper argues that resilience should be considered from a social approach that is sensitive to the context, including the relationships an individual has within their social environment. SUMMARY STATEMENT: What is already known about this topic? Many areas of nursing and health care are physically and emotionally taxing. Promoting resilience has been argued to be one possible strategy to mitigate the effects of working in these environments. Research to date has focused on what individual nurses need to be resilient and sustain working in potentially challenging health care environments. Recent research suggests that this may lead to victim blaming and foster a sense of failure in individual staff. What does this paper add? This paper offers an alternative perspective to exploring health professional resilience from a social approach. We argue there is a need to consider the close integration of nursing staff into the wider multidisciplinary team. In the context of an increasingly complex health system with limited resources, our paper highlights a unique perspective on how to address the need to promote resilience among nurses and other members of the health care workforce. The implications of this paper: for policy/practice/research or education: Promoting team resilience in a health care setting can lead to reduced compassion fatigue and burnout. A social approach to resilience fosters opportunities for all members of the health care team to flourish and be supported within the context of their work environment. Staff who are happy, enjoy their work and are able to thrive in their roles provide better quality care to patients and their families.